Intraoperative complications during total hip arthroplasty: a very uncommon intraoperative femur fracture occurred in a malnourished osteoporotic patient. - Zanzi, Alessandro; Ciatti, Corrado; Asti, Chiara; Caggiari, Gianfilippo; Cardinale, Umberto; Doria, Carlo; Pisanu, Francesco (Acta Biomedica Atenei Parmensis, 2023)
Intraoperative femoral fracture is a rare but growing complication of primary total hip arthroplasty. We aimed to present an uncommon related case, assessing also the role of malnutrition and osteoporosis. We discuss the case of a 49 years old male patient, malnourished and osteoporotic, with an intertrochanteric, multifragmentary, inveterate fracture, that happened three months before. During the prosthetic surgery, a supracondylar fracture occurred. We synthesized it with a 13 holes LISS plate, 7 distal screws and 3 proximal cerclage wires. The leg was immobilized to 0° for 3 weeks and the load forbidden for 3 months. Calcium, Albumine, Total Proteins, Osteocalcin and Vitamin-D levels were below the normal range. Teriparatide was administered for 6 months. Global investigation of the patient's nutritional status is recommended before joint replacement and preoperative planning is mandatory to choose the adequate implant. Osteoanabolic therapy could be advisable to favor fracture healing.